INSTRUMENTALIZATION AND IMAGINATION OF ETHNICITY: ARTVELISM AS AN INVENTED TRADITION - KIRCHANOV, Maxim (CENTRAL ASIA AND THE CAUCASUS, 2017)
The author analyzes the problems of Kartvelism as an invented political tradition in modern Georgia. This article uses inventionist approaches to examine the history and current trends in Georgian nationalism and identity. It is based on the principles proposed in 1983 by British historians Eric Hobsbawm and Terence Ranger in their book *The Invention of Traditions*. The author argues that Kartvelian myth has become an important and influential intellectual tradition, shaping cultural practices and social strategies. Various forms of Kartvelism are analyzed as an invented political tradition, including language and ideas related to the national mission. The article states that secondary and university education in history and philology has become a key channel for developing and promoting Kartvelism. The centralized system for teaching and popularizing the Georgian language, history, and literature helps maintain Kartvelism as an invented political tradition in contemporary Georgia. The Georgian language, history, and literature, along with their Kartvelian elements, are crucial in developing these political traditions, which Georgian intellectual and political elites use to build Georgian identity as both political and ethnic Kartvelian.